2020
DOI: 10.4252/wjsc.v12.i7.612
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cell therapy shows promising results for secondary lymphedema

Abstract: Lymphedema is mainly identified by progressive soft tissue swelling in impaired lymphatic system. Secondary lymphedema attributed to cancer therapy, parasite infection, and trauma remains a serious global disease. Patients with lymphedema suffer swelling, pain, and fatigue, with the dysfunction of the deformed extremities reducing the quality of life and increasing the risk of infection and lymphangiosarcoma. Adipose-derived stem cells (ADSCs) possess prominent regenerative potential to differentiate into mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Additionally, adipose-derived stem cells (ADSCs) have been demonstrated to possess stimulatory activity on lymphangiogenesis. [34][35][36] Our previous experience 33,37 indicated that BB implantation alone or cell injection alone may not be sufficient for treatment whereas a combination of BB scaffolds and seeded cells may substantially enhance the treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, adipose-derived stem cells (ADSCs) have been demonstrated to possess stimulatory activity on lymphangiogenesis. [34][35][36] Our previous experience 33,37 indicated that BB implantation alone or cell injection alone may not be sufficient for treatment whereas a combination of BB scaffolds and seeded cells may substantially enhance the treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Thread‐like BB scaffold has a multilumen structure and therefore, after implantation, it induces unidirectional interstitial capillary flow, which is driven by hydrostatic and oncotic pressure. Additionally, adipose‐derived stem cells (ADSCs) have been demonstrated to possess stimulatory activity on lymphangiogenesis 34–36 . Our previous experience 33,37 indicated that BB implantation alone or cell injection alone may not be sufficient for treatment whereas a combination of BB scaffolds and seeded cells may substantially enhance the treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies ( Takeda et al, 2015 ; Li et al, 2020 ), adipose-derived stem cells (ADSCs) could promote proliferation, migration, and tube formation of LECs in vitro by secreting various lymphangiogenic factors. In addition, it has been demonstrated that ADSCs can increase the number of lymphatic vessels and promote the restoration of lymphatic drainage in vivo ( Hayashida et al, 2017 ; Hu and Pan, 2020 ). Clinical research indicates that breast cancer survivors undergoing hormone therapy may be at an increased risk of poor fat graft survival during surgical reconstruction ( Zhu et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, no changes in arm volume were found in a follow up study (up to one year) as well as no significant improvement, being assessed via lymphoscintigraphy post-treatment with adipose-derived stem cells [ 109 ]. Hu et al (2020) report a new promising approach in secondary lymphedema treatment by using adipose-derived stem cells; however, this still needs to be evaluated in larger clinical studies [ 110 ].…”
Section: Overview Of Lymphedemamentioning
confidence: 99%